Romantic Relationship Dissolution, Microbiota, and Fibers - Chuang, Jie-Yu (Frontiers in Nutrition, 2021)
Microbiota inhabit nearly every part of our body with the gut microbiota representing the greatest density and absolute abundance. The gut-microbiota-brain axis facilitates bidirectional communication between gut microbiota and the brain. For instance, romantic relationship not only brings joy, it is also associated with increased gut microbiota diversity and health benefits whereas reduced microbiota diversity is related to obesity, cardiac disease, type 2 diabetes, and inflammatory disorders. Research has shown that dietary fibers may increase microbiota diversity and exert antidepressant effect. Among a plethora of life stressors, romantic relationship dissolution is a relatively common and painful experience that people encounter from time to time. Depressed mood, social isolation and poor intake are all associated with romantic relationship dissolution. In this article, it is hypothesized that romantic relationship dissolution is accompanied by decreased gut microbiota diversity which could be corrected with the ingestion of dietary fibers with an additional antidepressant benefit.